2012
DOI: 10.1186/1756-0500-5-128
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reference genes for expression analysis in the salivary gland and the intestine of Rhodnius prolixus (Hemiptera, Reduviidae) under different experimental conditions by quantitative real-time PCR

Abstract: BackgroundRhodnius prolixus is a blood-feeding insect that can transmit Trypanosoma cruzi and Trypanosoma rangeli to vertebrate hosts. Recently, genomic resources for invertebrate vectors of human pathogens have increased significantly, and R. prolixus has been one of the main species studied among the triatomines. However, the paucity of information on many of the fundamental molecular aspects of this species limits the use of the available genomic information. The present study aimed to facilitate gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 46 publications
2
62
0
Order By: Relevance
“…Previously, Actin has been considered to be one of the best reference genes for assessing gene expression in many insects [29], [30], and GAPDH was also frequently used as a reference gene [11], [31]. However, they were not the best reference genes in the present analysis and several studies have demonstrated that the stability of GAPDH expression was low in certain conditions [32].These results further suggest that the expression stability of reference genes is affected by different experimental conditions.…”
Section: Discussionmentioning
confidence: 72%
“…Previously, Actin has been considered to be one of the best reference genes for assessing gene expression in many insects [29], [30], and GAPDH was also frequently used as a reference gene [11], [31]. However, they were not the best reference genes in the present analysis and several studies have demonstrated that the stability of GAPDH expression was low in certain conditions [32].These results further suggest that the expression stability of reference genes is affected by different experimental conditions.…”
Section: Discussionmentioning
confidence: 72%
“…This gene was also reported to be the most stably expressed gene in larvae of the oriental leafworm moth Spodoptera litura under temperature stress and across different developmental stages (Lu et al, 2013) and in the head of the bee Apis mellifera infected with bacteria (Scharlaken et al, 2008). However, some other studies have reported reduced expression stability of this gene like in salivary glands of kissing-bug Rhodnius prolixus when infected with Protozoa Trypanosoma cruzi, in labial glands and fat body of the bumblebees Bombus lucorum and Bombus terrestris and across different life stages of the spider mite Tetranychus cinnabarinus (Hornakova et al, 2010;Paim et al, 2012;Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…Scharlaken [26] also identified GAPDH as the most stable gene in the head of the honeybee after bacterial challenge. However, several studies have demonstrated that the stability of GAPDH expression was low in certain conditions, such as certain life stages of Tetranychus cinnabarinus , in the labial gland and fat body in Bombus terrestris and Bombus lucorum , and in the salivary glands after Trypanosoma cruzi injection [17], [18], [25]. These results further suggest that the expression stability of reference genes is affected by different experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the described insect reference genes in literature, the NCBI database (http://www.ncbi.nlm.nih.gov) was searched for available S. litura sequences: ACTB [17], UCCR , FTZF1 , GAPDH [6], EF1 [2], [3] and AK [18]. We explored whether UCCR and FTZF1 could be used as reference genes.…”
Section: Methodsmentioning
confidence: 99%